2021
DOI: 10.21203/rs.3.rs-532891/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Galectin-3 as Prognostic Predictor in Patients with COVID-19 Acute Respiratory Failure

Abstract: Background. Galectin-3 is β-galactoside-binding lectin with several roles in immune-inflammatory response. To date, there is no evidence of Galectin-3 role as a prognostic predictor in COVID-19 disease. The aim of this study is to clarify the prognostic role of Galectin-3 in patients with COVID 19 acute respiratory failure.Methods. We enrolled 156 consecutive patients with COVID-19 disease. Routine laboratory test, arterial blood gas, chest X-ray or Computed Tomography and Galectin-3 dosage were performed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…With an area under the curve (AUC) of 0.622, Karsli et al ( 33) reported Gal-3 as a potential biomarker for the diagnosis of COVID-19. Prediction of ICU admission based on Gal-3 showed an AUC of 0.7 in the Portacci et al study (7), and 0.802 in Ozcan et al study (36). Moreover, the threshold of 15.51 ng/ml resulted in a sensitivity of 78% and specificity of 90% in the prediction of ICU admission, according to Kusnierz-Cabala et al (34).…”
Section: Diagnostic and Prognostic Use Of Gal-3mentioning
confidence: 89%
See 4 more Smart Citations
“…With an area under the curve (AUC) of 0.622, Karsli et al ( 33) reported Gal-3 as a potential biomarker for the diagnosis of COVID-19. Prediction of ICU admission based on Gal-3 showed an AUC of 0.7 in the Portacci et al study (7), and 0.802 in Ozcan et al study (36). Moreover, the threshold of 15.51 ng/ml resulted in a sensitivity of 78% and specificity of 90% in the prediction of ICU admission, according to Kusnierz-Cabala et al (34).…”
Section: Diagnostic and Prognostic Use Of Gal-3mentioning
confidence: 89%
“…The prediction of in-hospital mortality reported an AUC of 0.843 with sensitivity and specificity of 75% and 76.8%, respectively (36). The 30-day mortality prediction showed an AUC of 0.906 and 0.681 in studies by Portacci et al (7) and Tawiah et al (38). A study conducted by Rodrı ́guez-Tomàs et al (37) reported an AUC of 0.709 in differentiating COVID-19 patients from controls.…”
Section: Diagnostic and Prognostic Use Of Gal-3mentioning
confidence: 93%
See 3 more Smart Citations